The Agora, a Mark of Hellenisation? An Archaeological Note on Public Squares in Hellenised Mesopotamia and Parapotamia - Coqueugniot, Gaëlle (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
This paper proposes a preliminary survey of Greek-style agorai, i.e. public squares hosting political and economic activities, within the settlements of the Euphrates’ and Tigris’ valleys under Seleucid and Parthian rule (Figure 1). Although most of the sites considered were either urban settlements or new foundations from the late 4th century BCE, the evidence we will be dealing with dates mainly from the 2nd century BCE onwards, after the reinforcement of the Greek poleis under Antiochos IV, and continues after the Parthian conquest of the region between the 140s and 110s. From that period, we can detect in several sites a reinforced emphasis on the proclaimed Hellenic heritage of the ruling class, both in the epigraphy — with the mention of Greek-style institutions such as the boulê and the appearance of dynastic cults — and in the archaeological record.